2011
DOI: 10.1007/s10530-011-9954-5
|View full text |Cite
|
Sign up to set email alerts
|

Niche construction by the invasive Asian knotweeds (species complex Fallopia): impact on activity, abundance and community structure of denitrifiers and nitrifiers

Abstract: International audienceBig Asian knotweeds (Fallopia spp.) are among the most invasive plant species in north-western Europe. We suggest that their success is partially explained by biological and chemical niche construction. In this paper, we explored the microbial mechanisms by which the plant modifies the nitrogen cycle. We found that Fallopia spp. decreased potential denitrification enzyme activity (DEA) by reducing soil moisture and reducing denitrifying bacteria density in the soil. The plant also reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
98
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 56 publications
9
98
2
Order By: Relevance
“…Mincheva et al (2014) discovered that R. japonica litter decomposed 3-4 times more slowly than the litter of native grassland species. Dassonville et al (2011) and Tharayil et al (2013) found that R. japonica, or other species of the Reynoutria genus, decreased enzyme activities related to N mineralization and/or denitrification, although the changes were season dependent (Tharayil et al 2013). Our soils invaded by R. japonica, which is a nonmycorrhizal plant, showed a reduced abundance and species richness of arbuscular mycorrhizal fungi (AMF) (Zubek et al unpublished).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mincheva et al (2014) discovered that R. japonica litter decomposed 3-4 times more slowly than the litter of native grassland species. Dassonville et al (2011) and Tharayil et al (2013) found that R. japonica, or other species of the Reynoutria genus, decreased enzyme activities related to N mineralization and/or denitrification, although the changes were season dependent (Tharayil et al 2013). Our soils invaded by R. japonica, which is a nonmycorrhizal plant, showed a reduced abundance and species richness of arbuscular mycorrhizal fungi (AMF) (Zubek et al unpublished).…”
Section: Discussionmentioning
confidence: 99%
“…These species are considered transformers (Tokarska-Guzik et al 2010), i.e., invasive species that Bchange the character, condition, form, or nature of ecosystems over a substantial area^ (PyĆĄek et al 2004); therefore, their effects on soil microbial processes and thus soil functioning (Nannipieri et al 2003) require detailed investigations. Previous research has been often conducted using either one or a small number of study sites, a single invasive species/ genus, and/or measuring few microbial properties, making generalizations on the impact of the invasion on soil functioning problematic Herr et al 2007;Scharfy et al 2009Scharfy et al , 2010Aguilera et al 2010;Dassonville et al 2011;Tharayil et al 2013;Mincheva et al 2014). To the best of our knowledge, data on the influence of R. laciniata invasion on soil microbial properties are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, nitrogen resorption from senescing leaves appears to be less efficient in FS, although this result should be taken with caution as only one site was examined. The ability to efficiently recycle N from senescing leaves has been put forward as one of the key attributes of invasive knotweeds enabling them to outcompete the native flora (FJ: Dassonville et al 2011;FS: Urgenson et al 2009). In addition, low N concentrations in its litter result in very slow decomposition rates and N immobilization (Dassonville 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, very high stem elongation rate and the ability to quickly develop a dense canopy may impart a high competitive ability for light (Marigo and Pautou 1998). High nitrogen use efficiency may also be a key attribute of the complex (Dassonville et al 2011;Aguilera et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This study presents the following hypotheses. First, R. typhina can increase soil pH [25][26] because of the preferences of plant N required [27][28] and/or the alkaline substances in the litters and/or root exudations of invasive species [28][29]. Second, soil pH decreased under N fertilization [6][7][8] due to the release of free H + via the nitrifi cation process under N fertilization [30][31].…”
Section: Introductionmentioning
confidence: 99%